Induction of quinone reductase by withanolides - Misico, Rosana Isabel (2002)
Thirty-seven naturally occurring withanolides (1-37), previously isolated in our laboratories, were evaluated for their potential to induce quinone reductase with cultured murine hepatoma cells (Hepa 1c1c7). Spiranoid (29, 32) and 18-functionalized withanolides (2-5, 7-9, 24) were found to be potent inducers of the enzyme, while 5α-substituted derivatives exhibited weak activity. Preliminary studies were performed with compound 29 to evaluate enzyme-inducing capacity in multiple organ sites of BALB/c mice. Significant induction was observed in liver and colon, but not in lung, stomach, or mammary gland.